Identification of novel blood-based HCC-specific diagnostic biomarkers for human hepatocellular carcinoma - Li Yin; Na He; Chuizhe Chen; Nan Zhang; Yingzi Lin; Qianfeng Xia (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Introduction Hepatocellular carcinoma (HCC) ranks fourth in global cancer mortality, accounting for 8.2% of all cancer deaths. Early detection of HCC has a significant impact on clinical outcomes. The aim of this study was to identify blood-based biomarkers which are HCC-specific.Methods Comprehensive gene expression raw data of purified RNA of peripheral blood mononuclear cells (PBMC) was downloaded from GEO and was then analyzed. Differentially expressed genes (DEGs) in HCC were screened and the method of weighted gene co-expression network analysis was applied to identify candidate blood-based biomarkers associated with HCC.Results Three modules closely related to HCC were screened using WGCNA. Nuclear localization signal (NLS)-bearing protein import into nucleus biological process was the most significant enriched physiological process identified by MCODE, and 3 genes (DICER1, GMPS and NCOR1) were selected as biomarkers.Conclusion In our study, three novel blood-based HCC-specific diagnostic biomarkers for human hepatocellular carcinoma were identified. These findings may contribute to the non-invasive detection of early HCC patients.